HEALTH AND EDUCATION COUNSELING FOR COVID-19 VACCINATION IN DERMATOLOGY: HEALTH AND EDUCATION COUNSELING FOR COVID-19 VACCINATION IN DERMATOLOGY - Nopriyati .; Sarah Diba; M. Athuf Thaha (Conferences of Medical Sciences Dies Natalis, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been the cause of the Covid-19 pandemic in Indonesia since December 2019. As an effort to prevent the spread of Covid-19, the vaccination program has been implemented. Vaccination is a process in the body where a person becomes protected and to reduces the severity of diseases. Based on PERDOSKI recommendation 2021 for Covid-19 vaccination, several types of skin diseases need to be considered about the Covid-19 vaccine. By this time, hoaxes and misleading information about the Covid-19 vaccine had been spread widely. Adolescents are the target demographic of Covid-19 vaccination. With correct and adequate knowledge about the Covid-19 vaccine, they can invite their families and communities who have skin diseases around them to participate in the vaccination of Covid-19.